The Use of Aurix®100 Resin for the Selective Recovery of Gold and Silver from Copper, Gold and Silver Solutions - A. H. (Sandy) Gray; Tim Hughes; Jennifer Abols (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"The selective recovery of gold and silver from solutions containing other metals such as copper is possible using AuRIX®100 resin in conjunction with the Gekko Resin Column. Selectivity is driven by controlling the solution pH, which enables activities such as loading copper, gold and silver and then selectively stripping copper before gold and silver. Alternatively gold and silver can be loaded and the copper left in solution. The selective loading of gold while reducing the silver loading has also been demonstrated opening the possibility of producing high grade gold doré from high grade silver pregnant leach solutions. This paper reviews the AuRIX®100 resin and Gekko Resin Column Technologies, discusses the uses of AuRIX®100 in the recovery of gold and silver and the chemistry relating to several projects for which AuRIX®100 is being tested.INTRODUCTIONGekko SystemsGekko Systems specializes in the design, development and distribution of innovative mineral processing equipment and systems with a particular focus on gravity separation for the gold and diamond industries. The company, which has been around since 1996, has five main products: the InLine Pressure Jig, the InLine Spinner, the InLine Leach Reactor (ILR), Gekko Resin Column and Modular Systems.The InLine Leach Reactor is an intensive cyanidation reactor that uses high cyanide (0.5 – 2 % NaCN) and high oxidant (20 ppm dissolved oxygen as O2 or hydrogen peroxide) to dissolve gold from medium and high-grade gravity or flotation concentrates. The ILR, which typically replaces a shaking table in the gold room, is available in both batch and continuous models. There are 42 installations worldwide. Further details on this technology can be found in papers written by Gray et al (2003) and Longley, McCallum and Katsikaros (2003). By replacing a shaking table with an ILR, the overall gravity and plant recoveries can be increased significantly. Other advantages include reduced security risks, lower operating costs, reduced operator involvement due to the automatic process and increased safety for gold room operators."